EFFECTS OF SERVICE QUALITY, VALUE PERCEPTION AND LOYALTY ON CUSTOMER SATISFACTION: CASE OF A LOCAL RESTAURANT IN SOUTH BANDUNG, INDONESIA - Putu Nina Madiawati; Mahir Pradana; Sarah Miranda (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2021)
This study aims to determine how the Effect of Service Quality and Value Perception on Customer Loyalty through Customer Satisfaction as an intervening variable both partially and simultaneously. The method used in this research is descriptive and causality using quantitative methods involving 100 respondents who are customers of Chicken William restaurant in South Bandung, Indonesia. We conducted the research by taking a sample through non-probability sampling techniques with the type of purposive sampling. The analysis technique used in this study is Path Analysis using SmartPLS version 3. The results of the analysis show that Service Quality (X1) and Value Perception (X2) variables have a partial effect on Customer Satisfaction (Y), then Customer Satisfaction (Y) variables influence partial to Customer Loyalty (Z). Then simultaneously, there is the influence of Service Quality (X1) and Value Perception (X2) significantly influence Customer Satisfaction (Y). Then the intervening variable there is the influence of Service Quality (X1) and Value Perception (X2) directly affect Customer Satisfaction (Y), and this variable also influences Customer Loyalty (Z) indirectly through the Customer Satisfaction variable.